Penerapan Penilaian Autentik Berdasarkan Permendikbud Nomor 53 Tahun 2015 Di Sd Muhammadiyah 24 Gajahan Surakarta Tahun Pelajaran 2016/ 2017 - Setiyowati, Lilis, Drs. Mulyadi SK. SH., M.Pd (2017)
This research aims to: 1) describe the application of authentic assessment 2) know the authentic assessment implementation constraints 3) find out the solution in the authentic assessment of barriers based on Permendikbud Number 53 by 2015 in SD Muhammadiyah 24 Gajahan Surakarta in the academic year 2016/ 2017. This research used the qualitative approach with a descriptive qualitative research design. Data collection techniques used are observation, interview and documentation. Data analysis includes the reduction of the data, the presentation of data, and the with drawal of the conclusion. And test the validity of the data by triangulation of sources and methods. Based on the results of the study it can be concluded that teachers already apply authentic assessment based on Permendikbud Nomor 53 by 2015 but not yet perfectly especially on assessment skills. The barriers are that teachers felt the difficulty of doing a very authentic assessment of many types and the solution used is by following the workshop, training, studying with colleagues, friends sharing time supervision. Therefore, the application of authentic assessment conducted by the rudimentary skills of assessment, especially at then expected teachers can attend workshop, training, learning with colleagues, sharing time with the principal of supervision of execution of judgments of authentic, so that it can be implemented to its full potential.